Severe phenotype resulting from an active ring X chromosome in a female with a complex karyotype: characterisation and replication study. Issue 11 (November 1998) - Stavropoulou, C; Mignon, C; Delobel, B; Moncla, A; Depetris, D; Croquette, M F; Mattei, M G
Abstract : We report on the characterisation of a complex chromosome rearrangement, 46, X, del(Xq)/47, X, del(Xq), +r(X), in a female newborn with multiple malformations. Cytogenetic and molecular methods showed that the del(Xq) contains the XIST locus and is non-randomly inactivated in all metaphases. The tiny r(X) chromosome gave a positive FISH signal with UBE1, ZXDA, and MSN cosmid probes, but not with a XIST cosmid probe. Moreover, it has an active status, as shown by a very short (three hour) terminal BrdU pulse followed by fluorescent anti-BrdU antibody staining. The normal X is of paternal origin and both rearranged chromosomes originate from the same maternal chromosome. We suggest that both abnormal chromosomes result from the three point breakage of a maternal isodicentric idic(X)(q21.1). Finally, the phenotype of our patient is compared to other published cases and, despite the absence of any 45, X clone, it appears very similar to those with a 45, X/46, X, r(X) karyotype where the tiny r(X) is active.